Letter from Peter Golden to Patrick McCartan regarding McCartan's expenses, and discusses the political situation in Ireland and suggests that McCartan go to Washington as an ambassador - Golden, Peter, 1877-1926; McCartan, Patrick, 1878-1963; Irish Progressive League, New York (1919)
Golden asks "what is going to become of the Republic? Will it be shelved for that non-descript thing self-determination?". The letter also discusses a "Miss H[ughes].", who has been asking that "crowd about the [Irish National] Bureau and getting money for it without ever asking us or consulting us at all."
Letter inscribed on headed paper "Irish Progressive League, 229 Lexington Avenue, New York".
Keywords: Golden, Peter, -- 1877-1926 -- Correspondence; McCartan, Patrick, -- 1878-1963 -- Correspondence; Hughes, Katherine Angelina, -- 1876-1925; Irish National Bureau (Washington, D.C.); Irish Americans -- Societies, etc; Ireland -- Foreign relations -- United States -- 20th century; United States -- History -- 1919-1933